(untitled) - Siegel, Marc (Hoboken, N.J., 2005)
Life today for citizens of the developed world is safer, easier, and healthier than for any other people in history thanks to modern medicine, science, technology, and intelligence. So why is an epidemic of fear sweeping America? The answer, according to nationally renowned health commentator Dr. Marc Siegel, is that we live in an artificially created culture of fear. In False Alarm, Siegel identifies three major catalysts of the culture of fear—government, the media, and big pharma. With fascinating, blow-by-blow analyses of the most sensational false alarms of the past few years, he shows how these fearmongers manipulate our most primitive instincts—often without our even realizing it. False Alarm shows us how to look behind the hype and hysteria, inoculate ourselves against fear tactics, and develop the emotional and intellectual skills needed to take back our lives.
Keywords: Kiểm soát xã hội,Fear,Social control,Sợ hãi; Social aspects,Khía cạnh xã hội